Enter & Inhabit: Sensing the City. (1st April 2023) - Brown, Natalie Garrett; Meehan, Emma; Voris, Amy; Kipp, Christian
This article outlines the practice of enter & inhabit, a UK, dance and photography collaboration in outdoor spaces which foregrounds a sensorial relationship to space and place. Photographic images and reflective writings from a three-year research council funded project entitled Sensing The City are shared as a means to offer insight into the artistic methodology of enter & inhabit. Credits Sensing The City Project Team: Natalie Garrett Brown, Amy Voris, Emma Meehan, Christian Kipp Photography: Christian Kipp Contributing Movement Artists (Postcards): Helen Poynor, Paula Kramer, Hilary Kneale, Sandra Reeve.